Legal Innovations to Advance a Culture of Health. Issue 4 (December 2015) - Hodge, James G.; Weidenaar, Kim; Baker‐White, Andy; Barraza, Leila; Bauerly, Brittney Crock; Corbett, Alicia; Davis, Corey; Frey, Leslie T.; Griest, Megan M.; Healy, Colleen; Krueger, Jill; Lowrey, Kerri McGowan; et al.
Abstract : As conceptualized by the Robert Wood Johnson Foundation and its partners, a culture of health centers on a society in which health flourishes across all populations and sectors. Law, among other tools, is critical to advancing a culture of health across multiple arenas. In this manuscript, Network for Public Health Law colleagues illustrate how legal innovations at all levels of government contribute to societal health. Examples include modern laws that promote healthy and safe low‐income housing, telemedicine reimbursement, paid sick and safe time, healthy food and beverages, reduced smoking rates, child vaccinations, universal pre‐k, adolescents' healthy sleep, overdose prevention, and medical‐legal partnerships.